Advancements in running shoe technology and their effects on running economy and performance - a current concepts overview - Hebert-Losier, K.; Pamment, M. (Sports Biomechanics, 2023)
Advancements in running shoe technology over the last 5 years have sparked controversy in athletics as linked with clear running economy and performance enhancements. Early debates mainly surrounded `super shoes` in long-distance running, but more recently, the controversy has filtered through to sprint and middle-distance running with the emergence of `super spikes`. This Current Concepts paper provides a brief overview on the controversial topic of super shoes and super spikes. The defining features of technologically advanced shoes are a stiff plate embedded within the midsole, curved plate and midsole geometry, and lightweight, resilient, high-energy returning foam that - in combination - enhance running performance. Since the launch of the first commercially available super shoe, all world records from the 5 km to the marathon have been broken by athletes wearing super shoes or super spikes, with a similar trend observed in middle-distance running. The improvements in super shoes are around 4% for running economy and 2% for performance, and speculatively around 1% to 1.5% for super spikes. These enhancements are believed multifactorial in nature and difficult to parse, although involve longitudinal bending stiffness, the `teeter-totter effect`, the high-energy return properties of the midsole material, enhanced stack height and lightweight characteristic of shoes.